Ultra-early response assessment in lymphoma treatment: [(18)F]FDG PET/MR captures changes in glucose metabolism and cell density within the first 72 hours of treatment - Mayerhoefer, Marius E. (Eur J Nucl Med Mol Imaging, 2018)
PURPOSE: To determine whether, in patients with Hodgkin lymphoma (HL) or non-Hodgkin lymphoma (NHL), [(18)F]FDG PET/MR can capture treatment effects within the first week after treatment initiation, and whether changes in glucose metabolism and cell density occur simultaneously. METHODS: Patients with histologically proven HL or NHL were included in this prospective IRB-approved study. Patients underwent [(18)F]FDG PET/MR before, and then 48–72 h after (follow-up 1, FU-1) and 1 week after (FU-2) initiation of the first cycle of their respective standard chemotherapy (for HL) or immunochemotherapy (for NHL). Standardized [(18)F]FDG uptake values (SUVmax, SUVmean) and apparent diffusion coefficients (ADCmin, ADCmean) based on diffusion-weighted MRI, and metabolic and morphological tumour volumes (MTV, VOL) were assessed at each time-point. Multilevel analyses with an unstructured covariance matrix, and pair-wise post-hoc tests were used to test for significant changes in SUVs, ADCs, MTVs and VOLs between the three time-points. RESULTS: A total of 58 patients (11 with HL and 47 with NHL) with 166 lesions were analysed. Lesion-based mean rates of change in SUVmax, SUVmean, ADCmin, ADCmean, MTV and VOL between baseline and FU-1 were −46.8%, −33.3%, +20.3%, +14%, −46% and −12.8%, respectively, and between baseline and FU-2 were −65.1%, −49%, +50.7%, +32.4%, −61.1% and −24.2%, respectively. These changes were statistically significant (P < 0.01) except for the change in VOL between baseline and FU-1 (P = 0.079). CONCLUSION: In lymphoma patients, [(18)F]FDG PET/MR can capture treatment-induced changes in glucose metabolism and cell density as early as 48–72 h after treatment initiation. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00259-018-3937-z) contains supplementary material, which is available to authorized users.